Effects of Tillage and Mulching on Maize Yield, Soil Water Content and Organic Carbon in Kirige, Tharaka-Nithi County. Kenya - Njogu, Evelyn W. (University of Embu, 2016)
Sustainable agricultural production in Kenya requires improvement of yields per unit of land while still conserving soil resources. Besides poor soil nutrient status, water is a limiting factor to crop production in the rain-fed farming systems of central highlands of Kenya. Hence, there is need to address soil water scarcity challenges in order to increase crop production. The objective of the study was to determine the effects of tillage and mulching on maize (Zea Mays. L) yield, soil water content and organic carbon of Humic nitisols in the central highlands of Kenya. The study was conducted in Tharaka-Nithi County, Meru South Sub-County at Kirege for two seasons (long rains 2014 and short rains 2014). Two mulch levels; removal (W) and retention (R) of crop residue were applied randomly to plots measuring 7 m by 7 m under two tillage methods; conventional tillage (CT) and minimum tillage (MT). The treatments arrangement was a split-plot laid down in a randomized complete block design. Data on soil organic carbon, soil moisture, grain and biomass yield was subjected to Analysis of variance (ANOVA) using the mixed model in SAS 9.3. The soil organic carbon content data at the beginning and end of the experiment was subjected to student t-test for pair wise comparisons using the mixed model in SAS 9.3. Difference between treatment means was tested using least significant difference at 5% level of significance. The results showed significant tillage (p=0.0042) and mulching (p=0.0255) singular effect on maize yield. Combining tillage and mulching significantly (p=0.039) increased maize stover and grain yields. Overall, conventional tillage with residue treatment gave the highest increase in stover yield by 72%. Minimum tillage with residue and without residue, increased grain yield by over 50% compared to conventional tillage with and without residue. In the short term, soil water was not significantly influenced singly by tillage and mulching but it was positively influenced by tillage and mulch combination. On average, minimum tillage with residue and without residue increased soil moisture content by 10 and 7%, respectively compared to control, while Conventional tillage with residue and without residue increased moisture by 4 and 3% respectively. Tillage alone significantly (p=0.01) affected soil organic carbon content while mulching alone did not. There was significant (p=0.01) increase in soil organic carbon under minimum tillage as opposed to the reduction under conventional tillage at the 0–0.2 m soil depth. Combining tillage and mulching resulted to higher soil organic carbon content. Minimum tillage with residue, increased soil organic carbon by 0.33% more than minimum tillage alone. Short-term implementation of minimum tillage and mulching under the soil and climate conditions prevailing in Kirege Tharaka-Nithi County enhances maize production while improving soil conditions in terms of soil moisture and organic carbon content.